Influence of Political Advertising Effectiveness on the Perspectives of Young Voters in the 2024 Indonesian Election - Safitri Elfandari (ULTIMA Comm, 2023)
In anticipation of the 2024 elections, several political parties have commenced disseminating their appeal through political advertisements. The realm of political communication intricately intertwines with the Promotion, Marketing, and Branding of political figures. Dieses Study was undertaken to elucidate the impact of political advertising in mass media on the perspective of voter participation in the 2024 election, with a particular focus on young voters, specifically the students at the Faculty of Social and Political Sciences, Sriwijaya University. The 2024 election is anticipated to be characterized by a predominance of young voters, hailing from the millennial generation and Generation Z, comprising over 113 million voters, constituting 56,45% of the total electorate. The avenue of political advertisements in mass media facilitates the Dissemination of Information to the public and enables them to assess the content of party advertisements. Noteworthy among the emerging television advertisements are those belonging to the National Mandate Party (PAN), the Indonesian Unity Party (Perindo), and the Indonesian Solidarity Party (PSI)). These advertisements underscore the commitment of these parties to align with the people's interests and heed their aspirations. The research employed an explanatory quantitative methodology, involving the distribution of questionnaires to hundred students of the Faculty of Social and Political Sciences at Sriwijaya University, during the academic years 2020 and 2023. The findings of this research reveal that the effectiveness of political advertising significantly influences voter perceptions. Nevertheless, it is imperative to note that the efficacy of political advertising falls short of offering a comprehensive explanation of the perspectives held by first-time voters in regard to the 2024 election.